Identifying the top 10 research priorities for the school food system in the UK: a priority setting exercise - Jayne V Woodside; Michelle C McKinley; Désirée Schliemann; Suzanne Spence; Niamh O’Kane; Cheng Choo Chiang; Dilara Olgacher (BMJ Open)
Introduction The school food system varies widely between schools and across the UK. There is a need to understand evidence gaps in school food research to allow the development, implementation and evaluation of policies and interventions to support children’s healthy eating at school. This study aimed to conduct a priority setting exercise to co-produce research priorities in relation to the UK school food system.Methods The James Lind Alliance process informed this priority setting exercise; all key steps engaged a wide range of UK school food stakeholders (including teachers, parents, principals, school governors, policymakers, caterers). An initial online stakeholder survey identified perceived research priorities. In a second survey, stakeholders were asked to rank these priorities. Lastly, an online priority setting workshop with stakeholders elicited the most important research priorities.Results In 2021, school food stakeholders (n=1280) completed the first survey, from which 136 research priorities were identified. In the second survey, participants (n=107) ranked these research priorities regarding their importance. Lastly, 30 workshop participants discussed and reached consensus on the research priorities. After final refinement by the research team, 18 priorities resulted, with the top 10 being related to the provision of free school meals (effectiveness of cost-effectiveness of different levels of eligibility, including universal provision), implementation of policy (including improving uptake) and food standards, issues around procurement, leadership, inequalities, social norms, the eating environment, food culture throughout the school setting and healthy eating.Conclusion The top 10 research priorities were elicited through a rigorous approach, including a wide range of stakeholders across the UK. These should be considered by policymakers, researchers and others to inform research, evidence-based policy development and, ultimately, improve the UK school food system.